Corelation between glucose level, lipid profile and risk of coronary heart disease associated with organophosphorus pesticide poisoning - Kale, Bhagwat (International Journal of Biological Research, 2014)
The aim of our research was to correlate blood glucose and serum lipid profile parameters with risk of coronary heart disease associated with organophosphorus pesticide poisoning. For the purpose of this, 50 patients of organophosphorus poisoning and 50 healthy controls were selected. Blood glucose and serum lipid profiles were estimated by using commercially available diagnostic kits. We found a significant decrease (p < 0.05) in serum TAG, serum HDL cholesterol and serum VLDL cholesterol. On other hand we found a significant increase (p < 0.05) in blood glucose, serum total cholesterol and serum VLDL cholesterol. Organophosphorus poisoning is also associated with increased free radical production. Free radicals oxidize LDL cholesterol and oxidized cholesterol is taken by macrophages to form foam cells. Foam cells are responsible for formation of atherosclerotic plaques. Such plaques reduce coronary artery lumen and thus blood supply to heart get reduced which enhances the chances of myocardial infarction. Here, decreased HDL and VLDL and increased LDL cholesterol in organophosphorus poisoning is associated with increased risk of coronary heart diseases. Hence, estimation of blood glucose and lipid profile play important role in the diagnosis of risk of coronary heart diseases in organophosphorus poisoning. Keywords: Organophosphorus, Acetyl cholinesterase, Lipid Profile, Acetylcholine, Glucose.